Liquidity and corporate governance - Tom Berglund (Journal of Risk and Financial Management, 2020)
This paper discusses the relationship between stock market liquidity and corporate governance. Both concepts are widely investigated from different angles in the literature. It is generally agreed that they are related so that better corporate governance implies higher liquidity for shares of listed companies. However, the importance of good corporate governance for the market liquidity of the share will differ depending on the characteristics of the firm's business. Good corporate governance will be particularly important in reducing agency problems in firms where the business is subject to a high degree of uncertainty. Proper corporate governance, in other words, matters most for firms where external assessment of the firm's business prospects is difficult, while it is less important for value creation in firms where the business is easier to understand.
Keywords: 330; asymmetric information; board composition; information disclosure; market microstructure; price informativeness